Quasi-Contract: A Comparative Analysis Between the United States of America and Indonesia - Sibarani, William Edward; Puspaningsih, Utami; Stefanie, Clarita (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
Since the Roman era, there has been a general consensus that no one should prosper at the expense of another. However, the development of variations in legal systems in the world means that many countries must continue to adapt to this situation to avoid legal loopholes. In certain situations, the complexity of obligations in society causes quasi-contracts to occur. As a country that follows the civil law constitutional framework, Indonesia still encounters difficulties in handling quasi-contract disputes, not only due to the absence of written regulations but also because previous court decisions do not bind Indonesia. In contrast, in the United States of America, the creation of law occurs through court decisions. However, this study also aims to deliver insight into the legal systems' orientations in those two nations and how they relate to restorative justice. Hence, the author will discuss how quasi-contract problems are resolved by explaining the comparison between the two legal systems. This study uses a comparative juridical method to analyze the judgment practices on quasi-contracts between the United States of America and Indonesia and recommends the urgency of issuing regulations to address these disputes.